Contribution to the coincidence of malignant tumours and some allergic manifestations. - Rohan, Pavel; Komenda, Stanislav (Biomedical papers, 2002)
Clinical observations during the past decades led us to the early empirical assumptions that adult patients affected by certain types of allergic manifestations may have a lower prevalence of malignant tumors. In order to test those observations as well as some contradictory reports, we conducted a retrospective study using 32 years of records and statistics of a medium-sized hospital (420 beds) at St. Mary's Hospital, a general, non-chronic, teaching hospital, affiliated with McGill University in Montreal. The study has been realized during two periods: (a) 1965-1989 and (b) 1990-1996.
Keywords: Retrospective study / Malignancy / Allergy or allergy-like manifestation / Frequency of occurrence /